Serum Carcinoembryonic Antigen (CEA) Levels in Oesophageal Carcinoma - Chauhan, S.L.; Bhatnagar, V.B.; Singh, V.S.; Asif Zaidi, S. (Asian Journal of Chemistry, 2010)
Serum CEA levels were determined on 45 patients with carcinoma of oesophagus. In normal healthy persons serum CEA levels ranged between 0.0–2.5 μg/ml. Serum CEA levels were significantly higher in oesophagus carcinoma and corresponded to the extent of disease and presence of jaundice.